Basic considerations on the acceptance of knowledge (2014)
Social representations are decisive in human life since they are the basis of the practices that become conventional in groups and favor to verify the consistency among what people think, say, and finally do. In a research context it does not seem to be different. That is why this paper provides some reflections on the acceptance of knowledge and on how it affects what is done in research. Besides, some reflections are made on the presence of diatribes, continuous and pronounced distancing between researchers and those who legitimize the production of knowledge. Accordingly, it is vital to defuse the situation for it becomes risky in the training of researchers.